Development of Augmented Reality Learning Media Based on Assemblr Studio Web for Grade VII Junior High School Informatics Subjects - Bella Anjani; Fetri Yeni J; Novrianti; Fitri Maiziani (Darul Yasin Al Sys, 2026)
Local Area Network (LAN) concepts in the seventh-grade Informatics curriculum are relatively abstract, making it difficult for students to understand network topologies, inter-device relationships, and data communication processes. This study aimed to develop Augmented Reality (AR)-based learning media using Assemblr Studio Web and evaluate its validity and practicality for teaching LAN concepts. The study employed a Research and Development approach based on the 4D model, comprising the define, design, develop, and disseminate stages. Conducted at SMP Negeri 4 Palupuh, the study involved one subject-matter expert, two media experts, and 24 seventh-grade students. Data were collected using validation sheets and practicality questionnaires and analysed through mean scores and percentages. The findings showed that the developed learning media obtained a material validity score of 4.46 and a media validity score of 4.74, both of which were categorised as highly valid. The practicality assessment yielded a score of 86%, indicating that the media was highly practical for classroom use. The AR-based media provided interactive visualisations of Bus, Star, and Ring network topologies, thereby facilitating students’ understanding of LAN structures, relationships among devices, and data communication processes. The study concludes that the developed AR learning media is valid and practical for use in seventh-grade Informatics instruction. These findings demonstrate the potential of AR technology to support the concrete visualisation of abstract concepts, promote interactive learning, and strengthen the pedagogical integration of digital technology in Informatics education.